Building Digital Trust in Sharia Fintech for Hajj Services - Wafiroh Dwi Adlha; Dwi Retno Novanti; Lely Ana Ferawati Ekaningsih; Ubaidillah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study analyzes the role and implementation of Islamic fintech in building digital trust and optimizing Hajj administration processes, using the Muamalat Digital Islamic Network (DIN) application as a case study. Employing a qualitative case study approach at Bank Muamalat's Genteng Sub-Branch Office, data was collected through methodological triangulation, including direct observation, in-depth interviews with the manager, funding staff, customer service representatives, and prospective pilgrims, as well as document analysis. Data were analyzed interactively through stages of data reduction, data display, and conclusion drawing. The Muamalat DIN application successfully builds digital trust through the convergence of Sharia principles (the wadīah yad dhamānah contract and oversight by the Sharia Supervisory Board) with technological transparency. The application functions as a driver of financial and spiritual inclusion by eliminating geographical barriers and facilitating the fulfillment of maqashid sharia, particularly hifzh ad-din (preservation of faith). High adoption rates are driven by perceptions of usefulness and ease of use, reinforced by community-based religious outreach strategies. A transformation in service culture is demonstrated through the synergy between the digital interface and the ethical values (akhlaq) embedded in customer service. The primary challenges identified are reliance on uneven internet infrastructure and system overload during peak periods. The implementation of Islamic fintech in Hajj services through Muamalat DIN represents a successful paradigmatic transformation that harmonizes Sharia compliance, inclusive technological innovation, and ethical service. Its success in building digital trust and facilitating worship establishes it as a significant model for developing value-based Islamic financial services in the digital era. Keywords : Sharia Fintech, Hajj Administration, Digital Trust.